EFFECT OF FEEDING FREQUENCY OF CHICKEN INTESTINE PASTE ON THE GROWTH AND SURVIVAL OF GLASS CATFISH (Kryptopterus lais) FINGERLINGS - Anisya Putri Elmira; Khairul Hadi; Rosyadi Rosyadi; Agusnimar Agusnimar (Politeknik Kelautan dan Perikanan Bone, 2026)
This study evaluated the effect of feeding frequency of chicken intestine paste on the growth and survival of Kryptopterus lais fingerlings. The experiment utilized a completely randomized design with five feeding frequency treatments (2, 3, 4, 5, and 6 times per day) and three replications over 21 days. Ten fingerlings weighing 0.09±0.01 g were stocked in each aquarium and fed at a rate of 10% of their body weight per day. Observed parameters included growth performance, feed efficiency, feed conversion ratio, survival rate, and water quality. The results showed that feeding frequency had a significant effect on growth performance (P<0.05). Feeding four times day⁻¹ resulted in the best performance, indicated by a weight gain of 0.12±0.01 g, length gain of 1.14±0.21 cm, SGR of 0.57±0.01% day⁻¹, feed efficiency of 47.56±3.45%, feed conversion ratio of 2.48±0.21, and survival rate of 76.67±15.28%, with all water quality parameters remaining within optimal ranges. Therefore, a feeding frequency of four times day⁻¹ is recommended to improve growth and feed efficiency during the nursery phase of Kryptopterus lais.